Top requirements on the SD-WAN security checklist. Issue 7 (July 2017) - Wood, Michael
Abstract : Any significant network upgrade presents a challenge for CIOs and CISOs. So much can go wrong – from delays due to transition downtime and user retraining, to potential loss of data. But often, the single biggest concern will be security. This is especially true when contemplating a fundamental change in networking architecture, such as a migration to software-defined networking (SDN). Any significant network upgrade presents a challenge. So much can go wrong – from delays due to transition downtime and user retraining, to potential loss of data. But often, the single biggest concern will be security. This is especially true when contemplating a fundamental change in networking architecture, such as a migration to software-defined networking (SDN). Michael Wood of VeloCloud explains how it is possible to reap the benefits of new technology while maintaining and even improving security through the correct implementation of SD-WAN.